2011
DOI: 10.1007/s00520-011-1125-9
|View full text |Cite
|
Sign up to set email alerts
|

Home care—a safe and attractive alternative to inpatient administration of intensive chemotherapies

Abstract: Administration of intensive chemotherapy regimens at home was feasible and safe. Quality of life was not affected; satisfaction of patients and relatives was very high. A psychosocial benefit was observed for patients and relatives. Furthermore, a cost-benefit of home care compared to hospital treatment was demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 22 publications
2
28
0
Order By: Relevance
“…Many patients and caregivers prefer the convenience of homeor community-based care, and empirical evidence confirms that several cancer treatments can be safely delivered outside of the hospital (Boothroyd and Lehoux 2004;Luthi et al 2012). Some services are also more cost effective when delivered in the community or in patient homes rather than in hospital (Boothroyd and Lehoux 2004).…”
Section: Focus 2: Care Outside Hospitalsmentioning
confidence: 99%
“…Many patients and caregivers prefer the convenience of homeor community-based care, and empirical evidence confirms that several cancer treatments can be safely delivered outside of the hospital (Boothroyd and Lehoux 2004;Luthi et al 2012). Some services are also more cost effective when delivered in the community or in patient homes rather than in hospital (Boothroyd and Lehoux 2004).…”
Section: Focus 2: Care Outside Hospitalsmentioning
confidence: 99%
“…There is an increasing interest in the administration of cancer treatment outside the hospital based on patient preferences, capacity issues in oncology day care hospitals facing an increasing number of patients and treatments, and the increased use of oral chemotherapy [17]. In a feasibility study of home-based chemotherapy, patient benefits of home care included increased comfort and freedom [18]. All the patients in the BELIS study who completed the questionnaire concerning the quality of care in the hospital and at home indicated that being treated at home with trastuzumab SC was beneficial to a large or very large extent.…”
Section: Discussionmentioning
confidence: 99%
“…Savings for chemotherapy administered at home has also been demonstrated in solid tumors like colorectal, non-small cell lung cancer with a decrease in expenses of up to 53 % for intensive chemotherapies mainly administered for hematological malignancies [4, 5, 17]. …”
Section: Discussionmentioning
confidence: 99%